2020
DOI: 10.1155/2020/1024926
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Artificial Neural Networks and Logistic Regression in the Evaluation of Risk for Dry Eye after Vitrectomy

Abstract: Supervised machine-learning (ML) models were employed to predict the occurrence of dry eye disease (DED) after vitrectomy in this study. e clinical data of 217 patients receiving vitrectomy from April 2017 to July 2018 were used as training dataset; the clinical data of 33 patients receiving vitrectomy from August 2018 to September 2018 were collected as validating dataset. e input features for ML training were selected based on the Delphi method and univariate logistic regression (LR). LR and artificial neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The results demonstrate the discriminatory capacity of tear osmolarity in DED with the logistic classifier algorithm achieving a high accuracy of 85%. The research concludes that ML is an efficient approach for DED detection using tear osmolarity variables [58] . Furthermore, Yang et al [59] conducted research on the application of ML models for predicting DED in post-vitrectomy patients.…”
Section: Typical Machine Learning and Deep Learningbased Methodsmentioning
confidence: 89%
See 3 more Smart Citations
“…The results demonstrate the discriminatory capacity of tear osmolarity in DED with the logistic classifier algorithm achieving a high accuracy of 85%. The research concludes that ML is an efficient approach for DED detection using tear osmolarity variables [58] . Furthermore, Yang et al [59] conducted research on the application of ML models for predicting DED in post-vitrectomy patients.…”
Section: Typical Machine Learning and Deep Learningbased Methodsmentioning
confidence: 89%
“…The researchers concluded that ML is an effective and resource-saving technique for DED detection that mitigates diagnostic biases. In another study, Cartes et al [58] employed ML algorithms, such as logistic classifier, naive Bayes, support vector machines, and random forests for classifying DED based on mean osmolarity records of 40 subjects (20 with DED and 20 normal). The results demonstrate the discriminatory capacity of tear osmolarity in DED with the logistic classifier algorithm achieving a high accuracy of 85%.…”
Section: Typical Machine Learning and Deep Learningbased Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ANN model has robust error tolerance; thus, it can be extensively used in the fields of prediction and analysis. [ 72 ] Furthermore, leveraging the potential of an ANN-based CDSS would assist health-care providers to make better decisions concerning COVID-19 (diagnosis, classification, etc.). Despite standard statistical approaches (e.g., logistic regression) that need further modeling processes, ANNs do not necessitate distributional assumptions.…”
Section: Discussionmentioning
confidence: 99%